Who Are You Writing for? Differences in Response to Blog Design Between Scientists and Nonscientists. Issue 1 (February 2018) - Gardiner, Anna; Sullivan, Miriam; Grand, Ann
Science blogs have been advocated as potential mediators between science and nonscientist readers; however, they are mostly read by other scientists, with little research on how blogs can be made more appealing for nonscientists. We compared four possible treatments of a science blog post (text-only, humor, images and video). Nonscientists recalled more information when images were included compared to humor, while scientists performed worse with text-only than with video. Nonscientists enjoyed the images treatment most, while scientists preferred the video treatment. Adding images to blog posts is recommended as an easy method of increasing recall and enjoyment among readers.